Ukrainian Experience In The Usage Of Profiling For Revealing Criminal Offenses - Podzolkova, Tetiana (Archives of Criminology and Forensic Sciences, 2023)
Profiling, as a modern technology, is widely employed in operational-investigative activities of law enforcement agencies for the detection and investigation of criminal offenses. This system, comprising social and psychological techniques, facilitates the diagnosis of personal characteristics, peculiarities of hidden motives, and the assessment of information. Moreover, it enables the prediction of scenarios, behavioral patterns, and communication styles in various situations. Criminal profiling holds particular significance in crafting a psychological portrait of a suspect involved in a series of crimes. However, the use of profiling in law enforcement presents certain challenges. Although a psychological profile and its utilization cannot serve as direct evidence in legal proceedings, they are successfully used in search, detective, and investigative activities to identify criminals and prevent crime. When employing the profiling technique to interact with individuals crossing state borders, operatives have the opportunity to identify criminal intentions or instances of criminal activity. Additionally, profiling can be applied to prevent illegal actions and ensure public safety at transportation infrastructure facilities and during cultural events.